Aktualisasi bentuk-bentuk patriotisme dari sudut demografi: kajian kes di Ibukota Jakarta - Kamrussamad, Mustahi Siame (2023)
The spirit of patriotism must be present in every individual in the society of a country because patriotism is a sense of love and a sense of belonging to the homeland. It is not just an expression of feelings but demands appreciation by every citizen. However, most people are often confused and do not see the importance of this spirit of patriotism to the survival of the country. In fact, with the development of the times, it is said that the spirit of patriotism among the Indonesian community is fading. Therefore, this study aims to assess the level of patriotism of Indonesian society, determine the forms of patriotism owned by Indonesian society and make a comparison of forms of patriotism based on demographics. The research model is based on Jon Hurwitz and Mark Peffley who set five dependent variables as forms of patriotism namely iconoclastic, symbolic, instinctive environmental, capitalistic and nationalistic symbolic patriotism. While the scope of the study is limited to the community of Jakarta where the selection of Jakarta is because it is the administrative center of Indonesia and inhabited by various levels of society. This study uses a crosssectional study design which is one of the non-experimental study methods or ex-post facto study. The results of the study showed that the level of patriotism of Indonesian society was at a high level with a mean value of 3.94 and a low standard deviation of 0.28. Indonesian society has a very high value of symbolic patriotism compared to other forms of patriotism. Apart from symbolic patriotism, the people of Jakarta also have a high spirit of patriotism for iconoclastic and instinctive environmental patriotism. However, Indonesian society has only a moderate spirit of patriotism for nationalistic symbolic patriotism and has a low spirit of capitalistic patriotism. In addition, the researchers also detected differences spirit of patriotism based on gender, education level, age and ethnicity. Women were found to dominate the spirit of patriotism higher than men for symbolic, capitalistic and nationalistic patriotism. Meanwhile, the Indonesian community who are educated up to the diploma level has a high level of patriotism for symbolic patriotism and also environmental patriotism. In terms of age, the elderly Indonesian society has a higher level of capitalistic and nationalistic patriotism compared to other age levels. In terms of ethnicity, it was found that the Javanese ethnic group dominated the other ethnic groups in terms of the high level of patriotism